Co-developing SHELTER (Safe, Healthy Environments and Local Transformation for Equity and Resilience) with families with lived experience of homelessness in the New York City shelter system: A community needs assessment and data collection protocol - Diana Margot Rosenthal; Kate Guastaferro; Jasia Kubik; Melody Goodman (PLoS ONE, 2026)
In January 2025, the nightly census revealed that over 120,000 people were staying in New York City (NYC) shelters, including more than 41,000 children, of whom almost half were aged 0–5 years. Children under five years old (under-5s) experiencing homelessness are especially vulnerable because the first five years of life are a critical period for child growth, including approximately 90% of brain development. Furthermore, under-5s experiencing homelessness have a higher risk for multiple adverse childhood experiences, developing chronic health conditions, and recurrent homelessness across the life course. Data available for under-5s experiencing homelessness is generally lacking, and what is available is of notably poor quality in the United States, leaving a wide evidence gap and an inability to determine the actual needs of this population. This proposed protocol employs community-based participatory research and was co-developed with families with under-5s who have lived experience of homelessness in NYC shelters. The aim is to determine what barriers exist in the physical and social environments to optimizing health and wellbeing (e.g., milestones, child mental health, parental mental health, safety) among under-5s living in NYC shelters. Using a sequential mixed-methods design, we propose to address a gap in the current literature by conducting an assets- and deficits-based health needs assessment comprising a quantitative survey and qualitative semi-structured interviews. In the long term, our objective is to enhance the quality and quantity of data for this vulnerable population, thereby laying the groundwork for the future co-development of a comprehensive, optimized intervention addressing the needs of under-5s experiencing homelessness.